2002
DOI: 10.4315/0362-028x-65.4.651
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Growth of Listeria monocytogenes in Cured Ready-to-Eat Processed Meat Products by Manipulation of Sodium Chloride, Sodium Diacetate, Potassium Lactate, and Product Moisture Content

Abstract: A central composite second-order response surface design was employed to determine the influences of added sodium chloride (0.8 to 3.6%), sodium diacetate (0 to 0.2%), potassium lactate syrup (0.25 to 9.25%), and finished-product moisture (45.5 to 83.5%) on the predicted growth rate of Listeria monocytogenes in cured ready-to-eat (RTE) meat products. Increased amounts of both sodium diacetate (P < 0.11) and potassium lactate (P < 0.001) resulted in significant reductions in the growth rate constants of L monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 16 publications
4
66
0
Order By: Relevance
“…All of these components may influence the potential spoilage and shelf life of the products. For example, combinations of potassium lactate and sodium diacetate, used to inhibit growth of the pathogen Listeria monocytogenes in these products, can also inhibit growth of spoilage microorganisms (Seman, Borger, Meyer, Hall, & Milkowski, 2002). Glass et al, (2002) and Seman et al (2002) determined that the lactate and diacetate combination is more effective in cured meat products than in uncured products.…”
Section: Cured and Uncured Ready-to-eat Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these components may influence the potential spoilage and shelf life of the products. For example, combinations of potassium lactate and sodium diacetate, used to inhibit growth of the pathogen Listeria monocytogenes in these products, can also inhibit growth of spoilage microorganisms (Seman, Borger, Meyer, Hall, & Milkowski, 2002). Glass et al, (2002) and Seman et al (2002) determined that the lactate and diacetate combination is more effective in cured meat products than in uncured products.…”
Section: Cured and Uncured Ready-to-eat Productsmentioning
confidence: 99%
“…For example, combinations of potassium lactate and sodium diacetate, used to inhibit growth of the pathogen Listeria monocytogenes in these products, can also inhibit growth of spoilage microorganisms (Seman, Borger, Meyer, Hall, & Milkowski, 2002). Glass et al, (2002) and Seman et al (2002) determined that the lactate and diacetate combination is more effective in cured meat products than in uncured products. Because of the nature of these uncured products, they will eventually be spoiled by a wide variety of microorganisms, including pseudomonads, lactic acid bacteria, enterococci, psychrotrophic Gram-negative bacteria, yeasts, and molds.…”
Section: Cured and Uncured Ready-to-eat Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrites with sodium lactate and sodium diacetate have been found to act synergistically against Listeria monocytogenes in cured meat products (Seman et al, 2002;Gill and Holley, 2003;Legan et al, 2004;USDA, 2006). Milkowski et al (2010) reported inhibitory activity of nitrites against L. monocytogenes, E. coli O157:H7, S. aureus, and Bacillus cereus in cured meat products.…”
Section: Microbiological Safetymentioning
confidence: 99%
“…Different growth rates might be obtained by testing in other environments and with L. monocytogenes from other sources (31). However, the cured, cooked ham used in this study met the requirements laid down in the Polish standard (26) and its manufacturing and chemical composition was typical for this kind of product.…”
Section: Discussionmentioning
confidence: 99%